ANALISIS SISTEM PENGENDALIAN BAHAYA CONVEYOR BELERANG DI PELABUHAN PT. PETROKIMIA GRESIK - Dewangga Aji Saputra (Universitas Airlangga, 2018)
A technical and administrative control effort should be undertaken to prevent or reduce the impact of workplace accidents. Workplace accidents can be caused by unsafe human behavior and unsafe working environment conditions. This study has a general purpose for analyzing the sulfur conveyor hazard control system in PT Petrokimia Gresik. This research is observational, where as according to the way of data taking and timing of data retrieval is included in cross sectional study. The object of this research is the concession hazard control system of PT Petrokimia Gresik. In this research, I use descriptive analysis technique. The data used in this study is the primary data obtained from observations and interviews and secondary data obtained from corporate documents. The time of this research was conducted on April 20, 2015 until May 20, 2015. The result of the analysis on sulfur conveyor hazard control system in general is good. Lockout and tag out already have the tools and procedures but in its application still less and need to be improved. Emergency stop and emergency pull cord have less than 25% damage thus can be categorized well. To safeguard the fire hazard is properly installed and has good physical condition. For conveyor safety is in accordance with the standard nf en standards 294. For safety signs should be added. Administrative control measures are well implemented. Companies are advised to improve safety control efforts as there are still some need to be upgraded to either category.Keywords: analysis, control, conveyor, hazard